Distribution function of a distance between two random points in an oval - Gečiauskas, E. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. Гячаускас. Функция распределения расстояния между внутри овалаE. Gečiauskas, Atstumo tarp dviejų ovalo vidaus taškų pasiskirstymo funkcija